2017
DOI: 10.1080/17453674.2017.1376514
|View full text |Cite
|
Sign up to set email alerts
|

High failure rate after internal fixation and beneficial outcome after arthroplasty in treatment of displaced femoral neck fractures in patients between 55 and 70 years

Abstract: Background and purposeThe treatment of patients between 55 and 70 years with displaced intracapsular femoral neck fracture remains controversial. We compared internal fixation (IF), bipolar hemiarthroplasty (HA) and total hip arthroplasty (THA) in terms of mortality, reoperations and patient-reported outcome by using data from the Norwegian Hip Fracture Register.Patients and methodsWe included 2,713 patients treated between 2005 and 2012. 1,111 patients were treated with IF, 1,030 with HA and 572 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 24 publications
4
61
0
Order By: Relevance
“…Large studies from registers can help us to find small differences in complications and patient-reported outcome thereby generating hypotheses for clinical studies. As an example, the above-mentioned question of CRIF versus ORIF seems very challenging to answer within the frames Tables Table 1 Non-elderly hip [51], [55] *Womac, 24 items, total 0-96 score § Pain, stiffness, physical function *1 study ‡ EQ-5D index, 5 items, (3L or 5L answer levels) converted into an index score of 0-1.0 # Mobility, self-care, usual activities, pain/discomfort and anxiety/depression ‡ Pre-fracture and 4 to 24 months [58], [51], [55] ‡ EQ-5D VAS, 0-100 score # From worst to best imaginable health state ‡ 4 to ≥ 12 months [58], [51] Patient satisfaction: ‡ VAS, 0-100 score § From very satisfied to very unsatisfied ‡ 4 to 12 months [58] Our recommendations for a minimum core outcome data set: Level of; return to work, sporting/leisure activities, other activities of daily living, hip-fracture related pain, limping; EQ-5D-3L, EQ-5D-VAS, and objectively assessed functional performance, e.g. evaluated by the Timed Up & Go or 10-meter gait speed test.…”
Section: The Need For Future Researchmentioning
confidence: 99%
“…Large studies from registers can help us to find small differences in complications and patient-reported outcome thereby generating hypotheses for clinical studies. As an example, the above-mentioned question of CRIF versus ORIF seems very challenging to answer within the frames Tables Table 1 Non-elderly hip [51], [55] *Womac, 24 items, total 0-96 score § Pain, stiffness, physical function *1 study ‡ EQ-5D index, 5 items, (3L or 5L answer levels) converted into an index score of 0-1.0 # Mobility, self-care, usual activities, pain/discomfort and anxiety/depression ‡ Pre-fracture and 4 to 24 months [58], [51], [55] ‡ EQ-5D VAS, 0-100 score # From worst to best imaginable health state ‡ 4 to ≥ 12 months [58], [51] Patient satisfaction: ‡ VAS, 0-100 score § From very satisfied to very unsatisfied ‡ 4 to 12 months [58] Our recommendations for a minimum core outcome data set: Level of; return to work, sporting/leisure activities, other activities of daily living, hip-fracture related pain, limping; EQ-5D-3L, EQ-5D-VAS, and objectively assessed functional performance, e.g. evaluated by the Timed Up & Go or 10-meter gait speed test.…”
Section: The Need For Future Researchmentioning
confidence: 99%
“…The age at which patients cease to be "young" is usually suggested to be 60-70 years, but is still debated. One study from the Norwegian Hip Fracture Register (NHFR) reported a high failure rate of 27% after internal fixation for displaced FNFs in patients aged 55-70 (56), and one recent study from Taiwan reported 84.1% complications in displaced FNFs in patients aged [50][51][52][53][54][55][56][57][58][59][60] years (57), suggesting that more patients should receive an arthroplasty.…”
Section: Displaced Femoral Neck Fracturesmentioning
confidence: 99%
“…A mortality rate of 8.4% (7/83) was recorded within one year after surgery. Among patients of the similar age, the mortality rate of those patients with PFFs was significantly higher than that of patients with femoral neck fracture but was nearly similar to that of patients with hip fracture [15,16]. Meanwhile, the Swedish National Arthroplasty Registry reported a 13.1% morality rate among patients with PFFs during the first year after their surgery, and this rate agreed with the findings of Fuchtmeier [17], who reported a 13.2% mortality rate among patients within one year after surgery.…”
Section: Discussionmentioning
confidence: 76%